การศึกษาคุณลักษณะภาวะผู้นำเชิงพหุวัฒนธรรมของนักศึกษาครูในสามจังหวัดชายแดนภาคใต้ - พัฒนพิชัย ปาลิดา สายรัตทอง; ตันตินาครกูล อำภาพรรณ; สาลีหมัด ขนิษฐา; อยู่ในศิล วัยวุฑฒ์ (Journal of Research and Curriculum Development, 2021)
This research and development aimed to develop an attribute of multicultural leadership and to create a tool to assess multicultural leadership in student teacher in Three Southern Border Province. The research was conducted 4 phases 1)to study information and to interview 11 person relates to attribute of multicultural leadership in student teacher in Three Southern Border Province 2)data from information and interview were used to synthesize attribute of multicultural leadership 3)to develop a tool to assess multicultural leadership in student teacher 4) to try out the tool with 29 third-year student teacher.Research findings: The attribute of multicultural leadership consisted 3 components 1) multicultural knowledge 2) multicultural attitude 3) multicultural skill, tool for each component are as multiple-choice exam, written response and assessment for classroom activities. The results of try out show that all of tools can assess multicultural leadership with statistical significance at the .05 level.